Monetary Policy and the Stock Price - Exchange Rate Nexus: New Insights from Influential African Economies - Alimi, Ahmed S.; Olaniran, Oladotun D. (Asian Development Policy Review, 2019)
The study examined the role of monetary policy in the stock price - exchange rate nexus in the three major financial markets in Africa between 2005 and 2017. Essentially, the study attempted to validate the trade balance approach (TBA) for the African stock markets and conducted analyses in the periods before and after the global financial crisis (GFC). The study focused on Nigeria, South Africa and Egypt and utilized data on nominal exchange rate, stock price, nominal interest rate and consumer price index sourced from the International Financial Statistics of the International Monetary Fund. The trend analysis revealed that stock price and exchange rate in South Africa moved in the same direction while the variables moved in different directions in Nigeria and Egypt. With the aid of the panel autoregressive distributed lag technique (PARDL), the study showed negative and significant relationship between exchange rate and stock price, validating the TBA for the full sample and the post GFC periods while the theory cannot be substantiated for the pre-GFC period.